Autogenous regulation of the RNA polymerase beta subunit of Escherichia coli occurs at the translational level in vivo. - Passador, L (1989)
A series of transcriptional and translational fusions of the gene for the beta subunit of RNA polymerase (rpoB) to the lacZ reporter gene have been constructed on lambda vectors. Both transcriptional and translational fusions carry the upstream rplKAJL ribosomal protein gene region, which contains the two strong promoters rplKp and rplJp responsible for the transcription of rpoBC. Monolysogens carrying either the transcriptional translational fusion were assayed for beta-galactosidase, providing a measure of the transcription or of both transcription and translation of rpoB, respectively. Translational fusion monolysogens which also carried a multicopy plasmid containing the beta and beta' genes (rpoBC) under the control of a regulatable promoter, exhibited a substantial decrease in the beta-galactosidase levels upon overproduction of beta and beta'. No significant effect was seen in comparable experiments with the transcriptional fusions. These results argue that in vivo, the synthesis of the RNA polymerase beta subunit is autogenously regulated by a translational mechanism. Furthermore, experiments with the overexpressing plasmids confirm the requirement for a portion of the rplL-rpoB intercistronic region in the vicinity of the RNaseIII processing site for the efficient translation of the beta subunit mRNA.